A New Isoflavanone from Desmodium oxyphyllum and Its Cytotoxicity - Wang, Huan; Yang, Juan-Xia; Liu, Gui-You; Lou, Jie; Li, Limei; Hu, Qiufen; Gao, Xue-Mei (Asian Journal of Chemistry, 2015)
A new isoflavanone, (3R) 4',7-methoxy-5-methoxycarbonyl-isoflavanone (1) was isolated from Desmodium oxyphyllum. This new compound was tested for its cytotoxicity against five human tumor cell lines (NB4, A549, SHSY5Y, PC3 and MCF7) and it showed potential cytotoxicity against NB4 and PC3 cell with IC50 values of 5.6 and 7.2 μM.